The many-headed hydra : sailors, slaves, commoners, and the hidden history of the revolutionary Atlantic - Linebaugh, Peter (Beacon Press, 2000)
"Long before the American Revolution and the Declaration of the Rights of Man, a motley crew of sailors, slaves, pirates, laborers, market women, and indentured servants had ideas about freedom and equality that would forever change history. The Many Headed-Hydra recounts their stories in a sweeping history of the role of the dispossessed in the making of the modern world."--Jacket